PENGARUH MACAM MULSA DAN KONSENTRASI PUPUK DAUN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BROKOLI PUTIH (Brassica oleracea var. Botrytis L.) VARIETAS KUSUMA - Tarwa Mustofa; Risa Nurlaili; M. Darul Anwar (Universitas Islam Kadiri, 2019)
Cauliflower has an important role for human health because it contains vitamins and minerals that are needed by the body. These vegetables can help the digestion process, neutralize acidic substances and facilitate defecation The purpose of this study was to determine the interaction of mulch types and concentrations of fertilizer leaves of Plantafol (5:15:45) on the growth and production of white broccoli plants (Brasssica olleracea var. Botrytis L.) Kusuma F1 varieties. The research was conducted in Tondomulyo Hamlet, Gadungan Village, Puncu Subdistrict, Kediri Regency with a altitude of 250 meters above sea level, with a tropical climate with an average temperature of 27ºC. The type of soil in Tondomulyo Hamlet is sandy clay with a soil pH of 6.0. The study was conducted from December 2016 to February 2017. The results showed that there was a very significant interaction between the type of mulch and the concentration of plantafol leaf fertilizer on the number of white broccoli leaves at the age of 35 days. And there was a real interaction between the type of mulch and the concentration of leaf fertilizer on the height of white broccoli plants aged 35 days, leaf area of ​​plants at the age of 35hst. There is a significant influence on the type of mulch used on the diameter of white broccoli at harvest. In combination treatment of silver silver plastic mulch with leaf fertilizer concentration of plantafol 5-15-45 2000ppm (M2D2) with an average flower weight of 462,10gram / plant.